Status keberlanjutan penyediaan air di Sub DAS Cikeruh, bagian hulu DAS Citarum, Jawa Barat - Riezcy Cecilia Dewi; Yayat Hidayat; Asep Suheri (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2023)
Water balance or water avalibility that is not equal with the increasing water demand is a problem often encountered in water resources. The Cikeruh sub-watershed is one of the upstream parts of the Citarum watershed which has a water deficit. These problems require policy options in realizing sustainable use of water resources. The research aims to analyze the index and sustainability status of water supply in the Cikeruh sub-watershed and determining sensitive attributes of each sustainability dimension, namely the ecological, economic, social and institutional dimensions. The data analysis method uses the MDS (Multi-Dimensional Scaling) with the Rapfish software. The data used includes primary and secondary data.. The instruments for collecting primary data were questionnaires and structured questions to stakeholders. The result show that the level of sustainability of water supply in the Cikeruh Sub-watershed is generally categorized as quite sustainable (57,68%). The results of leverage analysis describes ten attributes that affect the levels of sustainability, namely the maintenance of the catchment area, water availability, availability of funds, other economic resources, farmers' income, transfer of land ownership, community understanding, community participation, coordination between institutions, and cooperation. By optimizing the most sensitive attributes, the sustainability of water supply could be improved.